ANALISIS KONTRIBUSI PENDAPATAN WANITA PENENUN SONGKET TERHADAP PENDAPATAN KELUARGA PETANI PADI SAWAH TADAH HUJAN DI DESA CEMPAKA KECAMATAN CEMPAKA KABUPATEN OGAN KOMERING ULU TIMUR (JASEP, 2018)
Research this aim for men ghitung how many big income especially women who seek weaving songket for add income Family and calculate contribution to income family women who seek weaving songket inVillage Cempaka districts Cempaka East OKU District.Research have been implemented in Village Cempaka districts Cempaka East OKU District. The data collection location research held on month July 2017. Method The research in is Method Surveys. Method data used in research this is observation and Interview with questionnaire as tool data collection. The data used is the primary data is data obtained directlyfrom field with use questionnaire as tool collecting data and secondary data namely data obtained from agencies - related agencies in research this. Based on the results of research conducted in the Village District Cempaka Cempaka East Ogan Komering Ulu is Rp 3.655 million, - per year or 17 percent of the average total family income USD 26.2883 million, - per year.